PUBLIC PERCEPTION OF LIVE MUSIC CAFE LOVERS: A CASE STUDY OF CUSTOMERS OF BAMBU PURPLE RESTO MARELAN - Riki Andika; Asmyta Surbakti; Junita Batubara (RADJA PUBLIKA, 2025)
The purpose of this study was to analyze the perception of the public who enjoy live music in cafes, a case study of customers of Bambu Ungu Resto Marelan. This research method is qualitative. The subjects of the study were customers of Bambu Ungu Resto Marelan. Data collection techniques were observation and interviews. Based on the results of the study through observation and data analysis of the theme of the music show according to the perceptions of visitors at the Bambu Ungu Resto cafe, it can be concluded that: 1. Visitors' perceptions of the theme of the music show are based on the choice of music from the management which has a significant impact on the customer experience in the cafe. Visitors to the Bambu Ungu Resto cafe tend to like relaxed and easy-listening music, such as pop music that creates a warm atmosphere. Artists whose songs have calming melodies and positive lyrics are favorites of visitors because they are able to create an atmosphere that matches their mood and needs at that time. 2. Knowing what music is popular can help the cafe stay relevant and attractive to visitors. The atmosphere of visitors during the music show is also considered quite supportive. Overall, the theme of the music show that suits visitors' preferences tends to increase their satisfaction and experience in the cafe, one of which is with the theme of pop music.